U.S. Trends in Antiretroviral Therapy Use, HIV RNA Plasma Viral Loads, and CD4 T-Lymphocyte Cell Counts Among HIV-Infected Persons, 2000 to 2008 - Althoff, Keri N. (2012)
BACKGROUND: The U.S. National HIV/AIDS Strategy targets for 2015 include increasing access to care and improving health outcomes for persons living with HIV in the United States (PLWH-US). OBJECTIVE: To demonstrate the utility of the NA-ACCORD (North American AIDS Cohort Collaboration on Research and Design) for monitoring trends in the HIV epidemic in the United States and to present trends in HIV treatment and related health outcomes. DESIGN: Trends from annual cross-sectional analyses comparing patients from pooled, multicenter, prospective, clinical HIV cohort studies with PLWH-US, as reported to national surveillance systems in 40 states. SETTING: U.S. HIV outpatient clinics. PATIENTS: HIV-infected adults with 1 or more HIV RNA plasma viral load (HIV VL) or CD4 T-lymphocyte (CD4) cell count measured in any calendar year from 1 January 2000 to 31 December 2008. MEASUREMENTS: Annual rates of antiretroviral therapy use, HIV VL, and CD4 cell count at death. RESULTS: 45 529 HIV-infected persons received care in an NA-ACCORD–participating U.S. clinical cohort from 2000 to 2008. In 2008, the 26 030 NA-ACCORD participants in care and the 655 966 PLWH-US had qualitatively similar demographic characteristics. From 2000 to 2008, the proportion of participants prescribed highly active antiretroviral therapy increased by 9 percentage points to 83% (P < 0.001), whereas the proportion with suppressed HIV VL (≤2.7 log(10) copies/mL) increased by 26 percentage points to 72% (P < 0.001). Median CD4 cell count at death more than tripled to 0.209 × 10(9) cells/L (P < 0.001). LIMITATION: The usual limitations of observational data apply. CONCLUSION: The NA-ACCORD is the largest cohort of HIV-infected adults in clinical care in the United States that is demographically similar to PLWH-US in 2008. From 2000 to 2008, increases were observed in the percentage of prescribed HAART, the percentage who achieved a suppressed HIV VL, and the median CD4 cell count at death. PRIMARY FUNDING SOURCE: National Institutes of Health, Centers for Disease Control and Prevention, Canadian Institutes of Health Research, Canadian HIV Trials Network, and the government of British Columbia, Canada.